Pengungkapan Lingkungan, Profitabilitas dan Nilai Perusahaan - Iwan Setiadi; Yumniati Agustina (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
This study aims to examine the effect of environmental disclosures on firm value by using profitability as a moderating variable. The research sample is all companies listed on the Indonesia Stock Exchange. The sampling technique used in this study was purposive sampling, which consisted of 143 companies. The analysis of this study uses moderated regression analysis. The results of this study indicate that environmental disclosure has a positive and significant effect on firm value. Proability strengthens the influence of environmental disclosures on firm value. The more environmental information disclosed by the company, the higher the trust of stakeholders in the company, so as to encourage stakeholders to help and cooperate with companies in earning profits, the increase in profits encourages an increase in the value of the company itself. Keywords: environmental disclosure, profitability, firm value